MODIFICATION OF POLYMER BRICKS TO OBTAIN NEW PRODUCTS (Journal of Universal Science Research, 2023)
The article describes how to process secondary polymer wastes by adding special fillers to them, changing their properties, obtaining new polymer composites with important properties such as fluidity, melting and thermal conductivity.